Medicinal and Aromatic Plant Specimen Preserved at Herbal Museum, Brindaban Botanical Garden, Plant Research Center, Makawanpur District, Central Nepal - Budhathoki, Prativa; Parajuli, Raghu Ram; Thakur, Chandrakala (Journal of Plant Resources, 2022)
This paper documents the collected and preserved museum specimen of medicinal and aromatic plant of the Herbal museum, Brindaban Botanical Garden, Plant Research Centre, Makawanpur. Based on the literatures of specimen conserved at Herbal museum and the interview with some local people, the use pattern of the specimens was documented. A total of 196 species belonging to165 genera and 91 families were recorded. Majority of the museum specimens collected and preserved in herbal museum were from Makawanpur followed by Kapilvastu, Ilam, Dolpa and Mustang ranging from 90 m - 5000 m elevation. Herbs were the dominant species and Seed/fruits were the most useful parts. Majority of the species were mostly used for the treatment of gastrointestinal disorder. This study provides detailed information about the medicinal and aromatic plants specimens that have been preserved at Herbal Museum, Brindaban Botanical Garden, Plant Research Center, Makwanpur, Nepal.